(untitled) (MAUSAM, 1966)
Based on data for the period 1901-1950, the incidence of spells of ’no rainfall’ in Rajasthan West, during the southwest monsoon season (June to September), has been studied, with week as the unit period of time and district as the unit of area. It has been shown that (i) the number of dry weeks shows a loose negative relationship with total rainfall and the number of rainy days, (ii) there is a pulsating character in the rainfall during the southwest monsoon season, (iii) years with too many or too few rainless weeks are experienced by many districts simultaneously, (iv) prolonged spells of rainless period are common at the commencement and cessation of the season; the second week of August is also a critical period for the setting in of prolonged dry spells. During the period 1901-1950, in the extreme case, in Jaisalmer district in 1918, the whole of the southwest monsoon season was rainless except for 34 mm of rain in the second half of July, (v) Rajasthan West can be divided into three zones, viz., Zone’ A’ consisting of Churu, Nagore and Pall districts with least number of dry spells, Zone ’B’ consisting of Ganganagar, Jodhpur and Bikaner districts with the number of dry spells increasing and Zone ’C’ consisting of Jalore, Barmer and Jaisalmer districts with maximum number of dry spells, increasing the basis of the duration of dry spells and their number, an index of "Extreme drought" has been worked out and the districts of southwest Rajasthan has been graded accordingly.